2018
DOI: 10.1073/pnas.1713195115
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes required for Mycobacterium abscessus growth in vivo with a prominent role of the ESX-4 locus

Abstract: , a rapidly growing mycobacterium (RGM) and an opportunistic human pathogen, is responsible for a wide spectrum of clinical manifestations ranging from pulmonary to skin and soft tissue infections. This intracellular organism can resist the bactericidal defense mechanisms of amoebae and macrophages, an ability that has not been observed in other RGM. can up-regulate several virulence factors during transient infection of amoebae, thereby becoming more virulent in subsequent respiratory infections in mice. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(161 citation statements)
references
References 64 publications
7
151
3
Order By: Relevance
“…These possibilities are consistent with macroscopic observations of augmented biofilm formation and of rough colony morphology upon ESX-4 induction. Recently published work in M. abscessus found that ESX-4 subverts lysophagosomal maturation in macrophage and amoeba models of infection (34). Notably, an insertion in the M. abscessus sigM gene phenocopied mutations in esx4, further supporting our hypothesis that SigM's role in activating esx4 is conserved across mycobacterial species.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These possibilities are consistent with macroscopic observations of augmented biofilm formation and of rough colony morphology upon ESX-4 induction. Recently published work in M. abscessus found that ESX-4 subverts lysophagosomal maturation in macrophage and amoeba models of infection (34). Notably, an insertion in the M. abscessus sigM gene phenocopied mutations in esx4, further supporting our hypothesis that SigM's role in activating esx4 is conserved across mycobacterial species.…”
Section: Discussionsupporting
confidence: 84%
“…ESX-4 is the widely distributed and conserved progenitor of the ESX secretion system family (16). The annotated esx4 locus consists of seven genes in most mycobacteria, with an eighth (eccE 4 ) found in M. abscessus (34). The esx4 locus has been solely defined by gene homologs it shares with the other paralogous esx loci (22).…”
Section: Discussionmentioning
confidence: 99%
“…A dominant method of transmission of M. abscessus remains contested [10,11], with evidence for and against patient-to-patient transmission being the common route [8,1214]. M. abscessus is ubiquitous in the environment with its niche hypothesised to be free-living amoeba [15,16], but due to the difficulties in isolating the organism, little has been done to track environment-to-patient acquisition. Confirmation of direct patient-to-patient transmission is important as it influences management of high-risk patients it could increase the effectiveness of infection control interventions by directing the use of limited resources.…”
Section: Introductionmentioning
confidence: 99%
“…The deleterious impact of M. abscessus in the degradation of lung function in CF patients has also been well documented (26). To dissect important and specific mechanisms of pathogenesis and to identify virulence determinants, we recently screened a Tn mutant library in A. castellanii and uncovered genes essential for M. abscessus intracellular survival (39). This approach unraveled the crucial and unexpected role of the ESX-4 locus for intracellular survival and phagosomal escape (39).…”
Section: Discussionmentioning
confidence: 99%
“…massiliense in amoebae and MΦ. This led to the discovery of the role of the ESX-4 type VII secretion system (T7SS) in intracellular survival of M. abscessus (39). This genetic screen also disclosed the MAB_0855 gene, encoding a yet uncharacterized MmpL.…”
Section: Significancementioning
confidence: 99%